Comparison of Dexmedetomidine and Esmolol for Attenuation of Hemodynamic Responses to Laryngoscopy and Tracheal Intubation in Hypertensive Patients (Annals of Medical Research, 2021)
Aim: During general anesthesia, control of the airway is often provided with endotracheal intubation, as a result, larynx and trachea are stimulated and plasma concentrations of noradrenaline and adrenaline are increased. This increase in blood pressure and heart rate causing arrhythmias and has a negative impact on myocardial oxygen delivery and consumption. Many drugs used for the prevention response to increased sympathic activity in blood pressure and heart rate. It was aimed to evaluate the effect of dexmedetomidine versus esmolol regarding hemodynamic response to laryngoscopy and intubation on hypertensive patients during elective surgery.
Keywords: Dexmedetomidine; Esmolol; Laryngoscopy; Hemodynamic Response.